Students’ difficulties analysis in reading comprehension at the second grade of MTs Nurul Ikhlas - Fathur Rizki Asani (Balai Diklat Keagamaan Ambon, 2022)
Regarding to the basic competence of the second grade of junior high schools in Curriculum 2013, the pupils are supposed to comprehend the generic structure, social function, and language features in reading material (narrative, descriptive, recount, and so on). However, the students still have some difficulties in comprehending a text. This could be known by identifying some previous studies related to reading comprehension difficulties in Indonesia. They have problems in finding the main idea and specific information in the text, making inference, or identifying the meaning of the word. Thus, this paper tried to analyze the difficulties that the students faced when comprehending an English reading text, to determine the reasons why the students are having problems in those difficulties, and to examine how teacher can help the students to overcome the difficulties. This research used mixed method and was classified as descriptive research. The participants of this research consisted of the second grade students and an EFL teacher of MTs Nurul Ikhlas Ambon. Reading comprehension test, questionnaire, and interview were used by the researcher to collect the data. Then, the data were analyzed by using descriptive quantitative analysis; calculating the result of students’ reading comprehension test and calculating the scale of the questionnaire. Moreover, the qualitative data was done by describing the interview result. The research revealed three findings. Firstly, the difficulty that faced by the students when comprehending an English reading text was identifying vocabulary. Secondly, the students completely agreed that reading process, students’ background knowledge, language knowledge, and motivation were factors which influenced them to have problems in those difficulties. And lastly, the strategies that can be used by the teacher to overcome the difficulties were memorizing strategy, reciprocal teaching, question-answer relationship, and fun learning strategy.